Results and complications of bilateral limb lengthening in achondroplasia: a retrospective analysis - Verdoni, Fabio; Giorgino, Riccardo; Virgilio, Camilla; Nannini, Alessandra; Viganò, Marco; Curci, Domenico; Peretti, Giuseppe Michele; Mangiavini, Laura (Frontiers in Pediatrics, 2023)
Background: Achondroplasia is one of the main causes of disharmonic dwarfism. Patients with achondroplasia might have physical and psychological limitations due to their disproportionate stature. Surgical limb lengthening is the only practical option available to achieve a stature comparable to normal population range. The purpose of this study is to analyze results and complications of our lengthening protocol. Methods: A retrospective analysis was performed on 33 patients with achondroplasia (21 females and 12 males) undergoing simultaneous bilateral tibia or femur lengthening in four surgical stages from 2017 to 2021 (46 lengthening procedures, with a total of 56 tibias and 36 femurs). For each patient, patients' characteristics and antero-posterior and lateral radiographs were obtained. The following parameters were analyzed: duration of lengthening with external fixator, amount of lengthening, complications or events that influenced outcomes and the healing index (HI). Results: The average tibial and femoral gain was 7.9 cm and 6.9 cm, respectively.The tibiae achieved better results than the femurs (p = 0.005). Nineteen complications were reported for 92 segments (20.7%), and the variables influencing complications were: step (p=0.002) and fixation duration (p=0.061). Conclusions: Bilateral parallel lower limb lengthening in four surgical steps may be a viable technique in patients with achondroplasia.